2016
DOI: 10.3389/fpls.2016.00603
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Allocation of Stoloniferous and Rhizomatous Plant in Response to Resource Availability: A Phylogenetic Meta-Analysis

Abstract: Resource allocation to different functions is central in life-history theory. Plasticity of functional traits allows clonal plants to regulate their resource allocation to meet changing environments. In this study, biomass allocation traits of clonal plants were categorized into absolute biomass for vegetative growth vs. for reproduction, and their relative ratios based on a data set including 115 species and derived from 139 published literatures. We examined general pattern of biomass allocation of clonal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 86 publications
0
14
0
2
Order By: Relevance
“…Moreover, Cussans (1968) found that crops that close their canopy early were particularly competitive against E. repens and therefore suggested that E. repens is particularly sensitive to light competition. This could mean that E. repens is generally light-dependent and perhaps more so than the rhizomatous species studied by Xie et al (2016). However, the nature of resources such as nutrients and light are fundamentally different (Craine and Dybzinski, 2013), i.e.…”
Section: Light and Nutrient Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Cussans (1968) found that crops that close their canopy early were particularly competitive against E. repens and therefore suggested that E. repens is particularly sensitive to light competition. This could mean that E. repens is generally light-dependent and perhaps more so than the rhizomatous species studied by Xie et al (2016). However, the nature of resources such as nutrients and light are fundamentally different (Craine and Dybzinski, 2013), i.e.…”
Section: Light and Nutrient Limitationsmentioning
confidence: 99%
“…In a meta-analysis of stoloniferous and rhizomatous plants (not including E. repens), Xie et al (2016) found that rhizomatous plants were less sensitive to light limitations than nutrient limitations as light limitations did not greatly affect shoot biomass, while nutrient limitations significantly affected both above-and below-ground biomass. Our results, similarly to Williams (1971), indicate that light has a relatively strong and early effect on E. repens biomass acquisition, allocation and morphological traits such as tillering, while the effect of reduced nutrient supply on E. repens biomass acquisition appears later and is most pronounced when light is not limited.…”
Section: Light and Nutrient Limitationsmentioning
confidence: 99%
“…Drought exerts strong impacts on biomass allocation. From the conventional ratio-based perspective of allocation, the patterns of biomass allocation in relation to drought are still equivocal due to the sharp differences in the experimental conditions, treatment procedures, and plant materials among studies (Poorter et al, 2012;Wang, Taub, & Jablonski, 2015;Xie et al, 2016). For instance, Erice, Louahlia, Jose Irigoyen, Sanchez-Diaz, and Avice (2010) reported that with the increased soil aridity, leaf dry mass fraction (LMF) of Medicago sativa decreased by 30% on average; stem mass fraction (SMF), on the other hand, increased by 4% on average.…”
mentioning
confidence: 99%
“…Taking all of the above into consideration, we are concerned that although warming would lead to temporary and compensatory biomass increases at the community-level, other potential effects would hinder the ability to provide long-term ecosystem services for C stock, especially in grassland ecosystems [26,27]. In general, Warm D and plant features, i.e., phylogeny, therefore seems to need further consideration when estimating warming-induced biomass responses [8,11,12,28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing number of scholars have suggested that considering phylogenetic features (phylogenetic signal, clade age, etc.) in meta-analysis could avoid the possible confounding effects of phylogeny on the results [10][11][12]. However, these above-mentioned concerns remain limited in the estimation of warming-induced biomass responses in China.…”
Section: Introductionmentioning
confidence: 99%